2021
DOI: 10.1002/adhm.202101309
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hyaluronan Density on the Behavior of Breast Cancer Cells with Different CD44 Expression

Abstract: Molecular gradients are common in biosystems and play an essential role in physiological and pathological processes. During carcinogenesis, for example, hyaluronan (HA) homeostasis is dysregulated by cancer cells and the altered synthesis and degradation processes result in the formation of HA gradients within the tumor microenvironment. Herein, a platform is developed to study the biological role of HA gradient in breast cancer cells. Cells with different aggressiveness and expression of CD44-the main HA rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…It suggested that OPN and CD44 in protein coronas, as typical proteins related to adhesion and uptake of tumor cells, may promote nanovesicle internalization through OPN-integrin and CD44-mediated ligand-receptor binding 53 . To investigate the role of OPN and CD44 opsonization in cellular uptake, cilengitide (CL) was used to inhibit the interaction between OPN and integrins 54 , 55 , and free hyaluronic acid (HA) was pretreated with tumor cells for competitive binding with CD44 to impede the nanovesicle-CD44 interaction 56 , 57 . The uptake efficiency in both A549 and HeLa cells was reduced after CL or HA preincubation with tumor cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It suggested that OPN and CD44 in protein coronas, as typical proteins related to adhesion and uptake of tumor cells, may promote nanovesicle internalization through OPN-integrin and CD44-mediated ligand-receptor binding 53 . To investigate the role of OPN and CD44 opsonization in cellular uptake, cilengitide (CL) was used to inhibit the interaction between OPN and integrins 54 , 55 , and free hyaluronic acid (HA) was pretreated with tumor cells for competitive binding with CD44 to impede the nanovesicle-CD44 interaction 56 , 57 . The uptake efficiency in both A549 and HeLa cells was reduced after CL or HA preincubation with tumor cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CD44, a glycoprotein on the surface of the cell, participates in immune recognition, cell-to-cell and cell-to-matrix interactions, cell migration, and other processes. [74] HA is a promising ligand for targeting CD44-overexpressing breast cancer cells, such as MDA-MB-231 cells (Figure 5b). However, HA-modified drug carriers accumulate preferentially in the liver after systemic injection, thereby resulting in insufficient accumulation in tumor tissues.…”
Section: Cd44 Receptor Targetingmentioning
confidence: 99%
“…Both collagen I and HA are important ECM components of breast cancer TME. Previous studies in the literature have demonstrated that HA interacts with breast cancer cells via CD44 receptors [34] and the addition of HA can better mimic the biophysical and biochemical microenvironments in breast cancer ECM. [35,36] Therefore, we attempted to prepare a bioink composing both HA and collagen.…”
Section: Collagen-ha-pnipam (Ch) Bioink Maintained Noninvasive Epithe...mentioning
confidence: 99%